Filled and empty states of Zn-TPP films deposited on Fe(001)-p(1×1)O - Bussetti, Gianlorenzo; Calloni, Alberto; Yivlialin, Rossella; Picone, Andrea; Bottegoni, Federico; Finazzi, Marco (Beilstein Journal of Nanotechnology, 2016)
Zn-tetraphenylporphyrin (Zn-TPP) was deposited on a single layer of metal oxide, namely an Fe(001)-p(1×1)O surface. The filled and empty electronic states were measured by means of UV photoemission and inverse photoemission spectroscopy on a single monolayer and a 20 monolayer thick film. The ionization energy and the electron affinity of the organic film were deduced and the interface dipole was determined and compared with data available in the literature.
Keywords: inverse photoemission; metal-oxide film; OMBE; porphyrin

(untitled) - Gottfried, J. M. (Surf. Sci. Rep., 2015)

(untitled) - Szyszko, B.; Latos-Graźyński, L. (Chem. Soc. Rev., 2015)

(untitled) - Pratviel, G. (Coord. Chem. Rev., 2016)

(untitled) - Auwärter, W.; Écija, D.; Klappenberger, F.; Barth, J. V. (Nat. Chem., 2015)

(untitled) - Sil, D.; Rath, S. P. (Dalton Trans., 2015)

(untitled) - Fan, S.; Lu, X.; Sun, H.; Zhou, G.; Chanq, Y. J.; Wang, Z.-S. (Phys. Chem. Chem. Phys., 2016)

(untitled) - Hieringer, W.; Flechtner, K.; Kretschmann, A.; Seufert, K.; Auwärter, W.; Barth, J. V.; Görling, A.; Steinrück, H.-P.; Gottfried, J. M. (J. Am. Chem. Soc., 2011)

(untitled) - Smets, Y.; Stark, C. B.; Lach, S.; Schmitt, F.; Wright, C. A.; Wanke, M.; Ley, L.; Ziegler, C.; Pakes, C. I. (J. Chem. Phys., 2013)

(untitled) - Picone, A.; Riva, M.; Brambilla, A.; Calloni, A.; Bussetti, G.; Finazzi, M.; Ciccacci, F.; Duò, L. (Surf. Sci. Rep., 2016)

(untitled) - Bussetti, G.; Calloni, A.; Celeri, M.; Yivlialin, R.; Finazzi, M.; Bottegoni, F.; Duò, L.; Ciccacci, F. (Appl. Surf. Sci., 2016)

(untitled) - Castellarin-Cudia, C.; Borghetti, P.; Di Santo, G.; Fanetti, M.; Larciprete, R.; Cepek, C.; Vilmercati, P.; Sangaletti, L.; Verdini, A.; Cossaro, A.; Floreano, L.; Morgante, A.; et al. (ChemPhysChem, 2010)

(untitled) - Calloni, A.; Berti, G.; Brambilla, A.; Riva, M.; Picone, A.; Bussetti, G.; Finazzi, M.; Ciccacci, F.; Duò, L. (J. Phys.: Condens. Matter, 2014)

(untitled) - Cattoni, A.; Petti, D.; Brivio, S.; Cantoni, M.; Bertacco, R.; Ciccacci, F. (Phys. Rev. B, 2009)

(untitled) - Gao, W.; Kahn, A. (Org. Electron., 2002)

(untitled) - Ishii, H.; Seki, K. (IEEE Trans. Electron Devices, 1997)

(untitled) - Hill, I. G.; Rajagopal, A.; Kahn, A.; Hu, Y. (Appl. Phys. Lett., 1998)

(untitled) - Hill, I. G.; Rajagopal, A.; Kahn, A. (J. Appl. Phys., 1998)

(untitled) - Crispin, X.; Geskin, V.; Crispin, A.; Cornil, J.; Lazzaroni, R.; Salaneck, W. R.; Brédas, J.-L. (J. Am. Chem. Soc., 2002)

(untitled) - Berti, G.; Calloni, A.; Brambilla, A.; Bussetti, G.; Duò, L.; Ciccacci, F. (Rev. Sci. Instrum., 2014)

(untitled) - Picone, A.; Brambilla, A.; Calloni, A.; Duò, L.; Finazzi, M.; Ciccacci, F. (Phys. Rev. B, 2011)

(untitled) - Bertacco, R.; Ciccacci, F. (Phys. Rev. B, 1999)

(untitled) - Pierce, D. T.; Celotta, R. J.; Wang, G.-C.; Unertl, W. N.; Galejs, A.; Kuyatt, C. E.; Mielczarek, S. R. (Rev. Sci. Instrum., 1980)

(untitled) - Ciccacci, F.; Chiaia, G. (J. Vac. Sci. Technol., A, 1991)

(untitled) - Ciccacci, F.; Vescovo, E.; Chiaia, G.; De Rossi, S.; Tosca, M. (Rev. Sci. Instrum., 1992)

(untitled) - Finazzi, M.; Bastianon, A.; Chiaia, G.; Ciccacci, F. (Meas. Sci. Technol., 1993)

(untitled) - Chiaia, G.; De Rossi, S.; Mazzolari, L.; Ciccacci, F. (Phys. Rev. B, 1993)